KAJIAN PENGALIHAN HAK MORAL TERHADAP KARYA CIPTA LAGU YANG DIBELI MELALUI PERJANJIAN JUAL BELI DITINJAU DARI KITAB UNDANG-UNDANG HUKUM PERDATA Jo. UNDANG-UNDANG REPUBLIK INDONESIA NOMOR 28 TAHUN 2014 - Naiborhu, Yoshua Putra Dinata (Jurnal Ilmiah Dinamika Hukum, 2025)
The absolute nature of moral rights creates practical legal issues. Under the concept of a sales agreement, the ownership of the sold object is transferred from the seller to the buyer. Conversely, the concept of moral rights, as stipulated in Law Number 28 of 2014, dictates that moral rights cannot be transferred for any reason whatsoever as long as the creator is alive. The conceptual and juridical ambiguity arises from the contradictory nature of a copyright and/or copyrighted work sales agreement versus the absolute status of moral rights. The research methodology employed in this study is the normative juridical method. This method focuses on analyzing legal norms related to moral rights and sales agreements, specifically referencing Law Number 28 of 2014 (Copyright Law) and the Civil Code (Kitab Undang-Undang Hukum Perdata). Normatively, the creator's moral rights are perpetual and non-transferable to other parties, in accordance with the mandate of Law Number 28 of 2014, Articles 5 and 57. Nevertheless, within the context of private law, Article 5 of Law Number 28 of 2014 grants the creator the freedom to either maintain or waive these rights. If the agreement is reached consensually, the principle of pacta sunt servanda is applicable between the contracting parties. A clause involving the assignment of moral rights can render the agreement voidable (vernietigbaar) if it involves a violation of the subjective requirements (consent and legal capacity). This is particularly true if the consent was obtained through an abuse of circumstances (penyalahgunaan keadaan). A violation of this requirement indicates that the consent provided by the creator was not free and consensual.